A Model of Community Disaster Risk Management Based Environmental Education in the Special Economic Development Zone, “Tak” Province - Rataya Saraporn; Wee Rawang; Shutima Saeng-ngern; Patranit Srijuntrapun (Migration Letters, 2023)
The purpose of this research was to design a model of community disaster risk management based environmental education in the special economic development zone, “Tak” province, Thailand. A mixed method of quantitative and qualitative research was employed, and data were collected through a questionnaire distributed to 383 villagers, interviews with 28 local experts: representatives of local authority, private and civil society sectors, and small group discussions with 35 local leaders. The research findings revealed that flooding and agricultural damage were the main community disasters because the community topography was mostly basin and foothill plains. However, the villagers commonly presented moderate levels on disaster risk management learning, disaster risk management and disaster risk management participation. This was why they faced low efficiency on preparation for disaster risk management as most villagers confirmed that their community problems were lack of knowledge, understanding and local plan for disaster risk management. Based on these results, the model of community disaster risk management based environmental education in the special economic development zone, “Tak” province comprising 3 stages and 7 factors was designed. STAGE (1) Pre – disaster, included four factors: Factor (1) Analyzing the community situation; Factor (2) Identifying the community disaster; Factor (3) Assessing the community capacity; and Factor (4) Selecting the approaches of disaster risk management. STAGE (2) During – disaster, included a factor: Factor (5) Collaborating the internal and external community, and STAGE (3) Post – disaster, included two factors: Factor (6) Building the community networks; and Factor (7) Developing the community capacity. Moreover, the designed model presented the high efficiency (x ̅ = 7.84) and positively affected community learning for pre-during-post disaster preparation in the community.